Financial Economics : A Concise Introduction to Classical and Behavioral Finance - Hens, Thorsten; Rieger, Marc Oliver (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2019)
Financial economics is a fascinating topic where ideas from economics, mathematics and, most recently, psychology are combined to understand financial markets. This book gives a concise introduction into this field and includes for the first time recent results from behavioral finance that help to understand many puzzles in traditional finance. The book is tailor made for master and PhD students and includes tests and exercises that enable the students to keep track of their progress. Parts of the book can also be used on a bachelor level. Researchers will find it particularly useful as a source for recent results in behavioral finance and decision theory.
Foundations: Introduction -- Decision Theory -- Financial Markets: Two-Period Model: Mean-Variance Approach -- Two-Period Model: State-Preference Approach -- Multiple-Periods Model -- Advanced Topics: Theory of the Firm -- Information Asymmetries on Financial Markets -- Time-Continuous Model. Appendices: Mathematics -- Solutions to Tests -- Index.
Description based on publisher-supplied MARC data.
Keywords: Decision making; Economic theory; Economics, Mathematical; Finance; Macroeconomics; Microeconomics; Operations research; Macroeconomics/Monetary Economics//Financial Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Finance, general; Microeconomics; Operations Research/Decision Theory; Quantitative Finance